PERAN AFRICAN UNION (AU) MELALUI AN AFRICAN UNION MISSION IN SOMALIA (AMISOM) DALAM KONFIK DI SOMALIA - Yesinta Valentina; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to analyze how An African Union Mission in Somalia (AMISOM) peacekeepers made efforts to resolve the conflict in Somalia from 2007 until 2012. Somalia's conflict involves transitional Federal Government (TFG) assisted by the An African Union Mission in Somalia (AMISOM) with Islamic Court Union (ICU) and Al-Shabaab. In addition, Ethiopia is also involved in the conflict. Somalia's conflict attracts international attention. African Union (AU) as a regional organization plays an important role to resolve conflicts that occur in the territory of its member states. The UN also decided to participateto resolve conflicts in Somalia.The data used in this study a secondary data. Secondary data was obtained through library research, and search online media research. The writer uses of the pluralism perspectiveand organization level of analysis. Theories used in this study is based on the organization theory by Clive Archer. The research result is indicate that in resolving the Somali conflict, the UN Security Council mandates the African Union (AU) as a regional organization to establish peace operations that is African Union Mission in Somalia (AMISOM). African Union Mission in Somalia (AMISOM) carries out a mandate as a peacekeeping mission in Somalia, so that the government can run as it should and people can live without fear of potential recurrence of conflict in the country. African Union Mission in Somalia (AMISOM) also acts as extension of international organizations in providing humanitarian assistance to the people of Somalia. These things make AMISOM an important element in efforts to restore security stability in Somalia. Although in the implementation of the effort, African Union Mission in Somalia (AMISOM) has obstacles that hinder the realization of peace mission in Somalia.Keywords : Conflict, Role, African Union (AU), African Union Mission in Somalia (AMISOM), Transitional Federal Government (TFG), Islamic Court Union (ICU), Al Shabaab.